Analysis of Public Administration’s Continuous Training Programs. A Case Study - Rodríguez-Fernández, Juan Ramón (2022)
Objectives. This research aimed to meet 3 objectives: 1) to analyze, in depth, the planning model for training developed by the Asturian Institute of Public Administration Adolfo Posada, in the North of Spain; 2) to point out the implications that this type of training design can have for the development of permanent training of people employed in the public sector in administrations; 3) to propose training alternatives based on the limitations found. Methodology. The research strategy and the methodological tools are rooted in the qualitative tradition. The research strategy deployed was a case study, and the main tools to collect information were interviews, document analysis, and bibliographical revision of the scientific literature. This research used the following analytical categories: teacher role, didactic methodologies, objectives, contents, and pedagogical materials. Results. One of the main results of this case study research was to confirm that the training planning model followed the principles of the technological model. This technological training model has some limitations regarding participants’ active participation or transferability of the training. Conclusions. In order to overcome these limitations, the last part of the paper proposes some alternative principles for training planning in public administrations.